(untitled) (Sociología y tecnociencia, 2013)
International mobility has become increasingly common in the research profession, partly due to strong policy support. To understand this trend, it is necessary to explore how researchers plan and envisage their career, that is, what drives their decisions. In this exploratory paper we shed light on this issue, comparing career drivers across three mobility categories. Furthermore, we take into account gender and the parental status of the researchers, as both factors remarkably influence career choices. We use data from the Study on International Mobility and Researchers’ Career Development Project (SIM-ReC), launched in 2011 by the Institute of Prospective Technological Studies (IPTS) in collaboration with NIFU (Norway), Logotech (Greece) and the University of Athens. The dataset covers researchers working in European universities across ten countries: Belgium, France, Germany, Italy, the Netherlands, Poland, Spain, Sweden, Switzerland and the UK. The results highlight how different mobility patterns reflect different motivations and confirm that gender and parenthood are critical in shaping career decisions.